Illusion Optics: Disguising with Ordinary Dielectric Materials. Issue 6 (13th December 2018) - Liu, Yichao; Guo, Shuwei; He, Sailing
Abstract: Illusion devices are usually designed using transformation optics. Here, a new method is proposed to achieve optical illusions without external devices by elaborately manipulating the scattering potential of an object. In contrast to the conventional transformation optics method, which completely replaces one object by the image of another object using complementary estoring media and a superlens, the method described here is more of a cosmetic operation for an object, which modifies the scattering pattern of the object to mimic another object by exchanging their scattering potentials in two symmetrical areas in the wave vector domain. Only positive isotropic nonmagnetic materials are introduced in the present method, which is impossible using the conventional method because superlenses require negative‐index materials. Both numerical simulations and experimental demonstrations are used to verify the performance of the illusion devices of this method. Abstract : An illusion optics method is proposed. This method is more of a cosmetic operation for an object, which modifies the scattering pattern of the object to mimic another object by exchanging their scattering potentials in the wave vector domain. Only positive isotropic nonmagnetic materials are introduced in the present method, which is impossible using the conventional transformation‐optics‐based method.